Kajian Peran Infrastruktur dalam Pengembangan Ekonomi Wilayah - Fitriani, Fitriani; Hukmi, Anindiya (Gema Cendekia Institute, 2025)
Infrastructure development plays a strategic role in driving regional economic growth in Indonesia. Adequate infrastructure can improve connectivity, increase the efficiency of goods and services distribution, and encourage investment. This study aims to examine the role of infrastructure in regional economic development in Indonesia by 2025, with an emphasis on interregional connectivity, equitable development, and strengthening regional competitiveness. The method used is a literature review with a descriptive-qualitative approach. The results show that the development of transportation, energy, telecommunications, and logistics infrastructure has had a positive impact on increasing productivity and economic inclusion. However, challenges remain in the aspects of equitable development, budget constraints, and cross-sector coordination. This study recommends accelerating region-based infrastructure development and strengthening synergies between the central government, regional governments, and the private sector.